EXTH-07. AN ANTISENSE OLIGONUCLEOTIDE AGAINST TUMOR MICROTUBES IN GLIOBLASTOMA AS A NEW THERAPEUTIC OPTION TO IMPROVE TUMOR SPECIFIC THERAPY. (14th November 2022) - Weil, Sophie; Azorín, Daniel Domínguez; Jung, Erik; Higgins, Josie; Mohammed, Hafeez; Reckless, Jill; Ramsden, Nigel; Keller, Peter; Grainger, David; Wick, Wolfgang; Winkler, Frank
Abstract: Glioblastomas are known to be highly therapy resistant tumors. The description of tumor microtubes (TMs) as long cellular protrusions that connect glioblastoma cells to a network resistant against all standard therapies advanced the basic biological understanding of the disease and offers a new therapeutic target. An antisense oligonucleotide (ASO) against the production of a protein involved in formation and function of TMs was developed and tested in a xenograft mouse model of human glioblastoma cells. After the implantation of fluorescent tumor cells under a chronic cranial window and the establishment of the tumor, the ASO treatment was started with a continuous micropump application directly into the central nervous system (CNS) and treatment effects were observed in a two-photon microscope. Furthermore, co-treatment with irradiation was tested and tumor size as well as protein expression evaluated in and ex vivo. This led to the conclusion that the setup of combined continuous pump application and two photon microscopy is technically feasible and tolerable. It offers the possibility of applying compounds directly into the CNS under live and longitudinal readouts. The fluorescently tagged ASO was traced in the brain parenchyma over weeks proving a high stability of the compound. In combination with radiotherapy, animals treated with the active ASO against the protein of formation and function of TMs showed a smaller tumor size than animals treated with radiotherapy and the non-targeting ASO. The targeted protein was expressed less in the treated animals then the animals receiving the control ASO and the extend of protein expression correlated with tumor size. Hence, after successful therapies with ASOs in other neurologic diseases and the need for better therapeutic options for glioblastoma patients, the development of an ASO against a protein involved in the TM formation and function offers a new therapeutic option with high translational potential.